Technology-Enhanced Language Learning (TELL) in an English as a Foreign Language (EFL) Classroom: A Substitution, Augmentation, Modification and Redefinition (SAMR) Framework - Isry Laila Syathroh, - (2021)
Rapid advancement of technology has affected many aspects of human's life. In educational context, it creates opportunities for teachers to deliver lessons by integrating technology in their classes. Through qualitative study, this research was done in one vocational school, involving one EFL teacher and 36 students. There were three research questions posed: 1) Viewed from SAMR framework, how is TELL implemented in an EFL classroom? 2) What are the challenges and their solutions when implementing TELL in the similar context? and 3) What are students' perceptions towards the implementation of TELL in their EFL classroom? To answer the questions, 14 meetings of classroom participatory observation were done. Then, retrospective interview was conducted to confirm the data. Students' perceptions were investigated through questionnaire. The first finding showed that, the EFL teacher utilized different technology (web-based and non web-based) tools including several technology applications, such as: learning management system (LMS) applications (e.g.: Google Classroom), language learning applications (e.g.: LyricsGaps, QR Code, and Speechnotes), game-based applications (e.g.: Kahoot and Akinator), poster & video-maker applications (e.g.: Canva and Kinemaster) and certain English language learning websites. About 79% (11 meetings) of technology integration activities were classified into augmentation activities (technology was substituted for certain traditional teaching tools, but with significant enhancements to students' learning experiences). Then 7% (1 meeting) of technology integration activity was classified into modification activities (technology integration requires a significant redesign of tasks). And 14% (2 meetings) of technology integration activity was classified into redefinition activities (technology allows for new tasks that were previously inconceivable with traditional teaching tools). The second finding revealed internal and external challenges during technology integration activities, e.g.: motivation, accessibility, support and training. Finally, the third result revealed that students positively perceived technology integration activities in learning English.